Improvement of Hot Mix Asphalt Resistance to Permanent Deformation at High Temperature Using Nanomaterial Modifiers: A Review (Journal of Engineering, 2025)
The integration of nanomaterials in asphalt modification has emerged as a promising approach to enhance the performance of asphalt pavements, particularly under high-temperature conditions. Nanomaterials, due to their unique properties such as high surface area, exceptional mechanical strength, and thermal stability, offer significant improvements in the rheological properties, durability, and resistance to deformation of asphalt binders. This research reviewed the application of various nanomaterials, including nano silica, nano alumina, nano titanium, nano zinc, and carbon nanotubes in asphalt modification. The incorporation of these nanomaterials into asphalt mixtures has shown potential to increase the stiffness and high-temperature performance, thereby reducing rutting potential and improving the overall lifespan of the pavement. The mechanisms by which nanomaterials enhance the thermal and mechanical properties of asphalt were explored. Furthermore, the challenges associated with their implementation were examined, as effective utilization is hindered by agglomeration, inconsistent dispersion, and dosage sensitivity, compounded by the absence of standardized guidelines and the variability in reported contents. The findings indicate that while nanomaterials hold considerable potential for improving high-temperature asphalt performance, further research is needed to optimize their use and fully realize their benefits in large-scale applications.